Does patient education improve compliance to routine diabetic retinopathy screening?. (April 2020) - Moinul, Prima; Barbosa, Joshua; Qian, Jenny; Chen, Mei Lin; Mohaghegh, Mohammad; Kaur, Harneel; Holmes, Julie; Radman, Heather; Robinson, Tammy; Chaudhary, Varun
Introduction: Diabetic retinopathy (DR) screening relies on adherence to follow-up eye care. This article assesses if a model of patient education and tele-retina screening among high-risk patients with DR can achieve increased rates of compliance within a one-year follow-up. Methods: Between May 2014 and May 2016, DR screening was conducted in a cohort of 101 patients with diabetes in Southern Ontario. Optical coherence tomography and fundus photography images were used to visualize the retina remotely. Enrolled patients participated in an educational seminar at the screening site with the expressed purpose of enhancing patient understanding of DR. A chi-squared test was used to assess patient compliance to follow-up examinations within 6–12 months, while pre-to post-screening HbA1c levels were compared using a dependent t -test. Results: Of 101 patients who completed the study, 33 patients (32.6%) have never previously been screened for DR. Baseline compliance to annual screening increased from 36 patients (35.6%) to 51 patients (50.5%) after the tele-retina programme ( p  = 0.03). Eighty-nine patients (88%) were referred to an optometrist for ongoing care compared with 12 patients (11.9%) to an ophthalmologist for management of DR. Overall, 100 patients (99.0%) were satisfied with the tele-retina screening. There was no significant change in pre- to-post screening HbA1c levels ( p  = 0.91). Discussion: Patient education-focused tele-retina screening for DR significantly increased compliance to follow-up in a high-risk, non-compliant patient population. Management of diabetes as captured by HbA1c levels remain unchanged in the cohort indicating a need for ongoing inter-professional collaboration in education and vision screening.